A conceitualidade do livro em literatura: desmesuras da página em Novalis, Mallarmé e Borges - Davidson de Oliveira Diniz (2014)
This dissertation discusses the symbolism of the book as compositional horizon for literature in modernity. From this extensive question, the thinking occurs in three movements. First, we investigate the significance of the book from the moment when the literary object left itself to conceptualize. Then, we reflect about the concept of literature, the literary language itself, as a specific formulation of epistemology that emerges in modernity. Finally, we argue if the possibility of the symbolism of the book (dated long before modernity) has been reworked in order to legitimize the composition plan and the language that the literature was limited in the aesthetic and modern knowledge field. For that, we live with three distant works in linear temporality, but close (or approachable) as constituents and intermediates of the hypothesis brought to discussion in these pages. It is the vindications of the book in Novalis , S. Mallarmé and J.L. Borges.